Driving Digital-Based Innovation Culture in Islamic Financial Institutions: Mediated by Job Satisfaction - Muhammad Ridwan; Aida Nur Mohd Kodri (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study examines the influence of digital training, technological competence, information accessibility, and electronic financial facilities on digital-based innovation culture, with job satisfaction serving as a mediating variable, within Islamic banking institutions operating in Padang, West Sumatra, Indonesia. Although digital transformation has been widely discussed in the financial sector, empirical evidence explaining how organizational support in digital initiatives shapes innovation culture through employee satisfaction in Sharia-based banking remains limited. This study addresses this gap by adopting Organizational Support Theory (OST) as the sole theoretical foundation. A quantitative research design was employed using a purposive sampling technique. Data were collected from 150 employees working in operational and financial units of Islamic banks that actively implement digital financial systems. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine both direct and indirect relationships among the variables. The results indicate that digital training, technological competence, information accessibility, and electronic financial facilities have significant positive effects on job satisfaction and digital-based innovation culture. Furthermore, job satisfaction partially mediates the relationship between digital organizational support and innovation culture, highlighting its role as a key psychological mechanism in transforming digital support into innovative behavior. These findings confirm the relevance of Organizational Support Theory in explaining how digital initiatives, when perceived as supportive, foster employee satisfaction and innovation in Islamic banking institutions. Strengthening perceived organizational support is essential for cultivating a sustainable innovation culture while maintaining alignment with Islamic principles.